Geothermal System of the Dieng-Batur Volcanic Complex - M.T. Zen (Institute for Research and Community Services (LPPM) ITB, 1971)
This paper is mainly concerned with the evaluation of reports on geophysical and geochemical surveys made by Group Seven Inc. and Truesdell in the Dieng Mountains under contract with US-AID and on behalf of the Directorate General for Power and Electricity and the Indonesian Geological Survey and partly also with the author's own field observation on geothermy in the Dieng Mountains in Central Java. All the accumulated data lead to the conclusion that the geothermal system of eastern Dieng originated through the intersection of two major fracture zones. The high chloride content found in various streams gives good reason to accept that the geothermal system of the Dieng Mountains is a system of hot water and steam rather than a system of dry steam only. The hot springs in the Dieng Mountains might represent surface manifestation of a deep, neutral, hot water